To simplify the expression \( 3.2(x-2) + 7.2(-x-1) \), we will first distribute the constants to the terms inside the parentheses.
-
Distribute \( 3.2 \) to \( (x-2) \): \[ 3.2(x-2) = 3.2x - 6.4 \]
-
Distribute \( 7.2 \) to \( (-x-1) \): \[ 7.2(-x-1) = -7.2x - 7.2 \]
Now, we combine these results: \[ 3.2(x-2) + 7.2(-x-1) = (3.2x - 6.4) + (-7.2x - 7.2) \]
Next, we combine the \( x \)-terms: \[ 3.2x - 7.2x = -3.2x \]
Now combine the constant terms: \[ -6.4 - 7.2 = -13.6 \]
Putting it all together, we have: \[ 3.2(x-2) + 7.2(-x-1) = -3.2x - 13.6 \]
Thus, the expression equivalent to \( 3.2(x-2) + 7.2(-x-1) \) is: \[ \boxed{-3.2x - 13.6} \]